Down-regulation of class I HLA antigens and of the Epstein-Barr virus-encoded latent membrane protein in Burkitt lymphoma lines. - Masucci, M G (1987)
Epstein-Barr virus (EBV)-carrying Burkitt lymphoma (BL) cells are relatively or completely resistant to the lytic effect of major histocompatibility complex class I HLA antigen-restricted cytotoxic T lymphocytes (CTLs) generated by stimulating lymphocytes of EBV-seropositive donors with the autologous EBV-transformed lymphoblastoid cell line (LCL). We previously found that EBV-negative and EBV-carrying BL lines derived from HLA-A11-positive donors were not only resistant to lysis by the HLA-A11-restricted CTL generated by stimulation with the autologous LCL, but also to HLA-A11-specific CTL derived from lymphocytes of an EBV-seronegative donor stimulated with an allogeneic LCL. Using the same and additional cell lines, we now show that the CTL resistance of the BL lines is probably due to a selective down-regulation of HLA-A11. We also show that the EBV-encoded latent membrane protein is expressed at a lower level in the EBV-carrying BL lines than in EBV-transformed LCLs. Only one of eight in vitro EBV-converted BL lines that shifted to a more LCL-like growth pattern expressed LMP at a high level. This line also reexpressed the HLA-A11 antigen that was undetectable in its EBV-negative progenitor. Our findings suggest that the typical BL cell phenotype is associated with low expression of both proteins.